2020
DOI: 10.1111/ijfs.14839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic treatment on peanut protein isolate‐oat dietary fibre mixture gels induced by transglutaminase

Abstract: The effects of ultrasonic treatment on the physicochemical properties of transglutaminase-induced gels prepared by the mixture of peanut protein isolate (PPI) and oat dietary fibre (ODF) were investigated. The gel strength and water holding capacity (WHC) of PPI gels and PPI-ODF mixture gels were enhanced after ultrasonic treatment, and ultrasonic PPI-ODF mixture gels had higher gel strength and WHC than ultrasonic PPI gels. The ultrasonic treatment of mixture gels increased the storage modulus, loss modulus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…As earlier, addition of polysaccharides improved the WHC of propylene glycol alginate–zein, 32 corn starch–black bean protein isolate, 50 peanut protein isolate–oat dietary fiber, 59 and ginkgo seed protein–pectin (0.1–0.5%). In addition to poor water entrapment ability (48.46–59.39%) of ginkgo seed protein compared to other plant-derived protein gels (soy or cowpea proteins), introduction of 1% pectin decreased the WHC of ginkgo seed protein–pectin gels.…”
Section: How Do Protein–polysaccharide Interactions Affect the Functi...supporting
confidence: 63%
“…As earlier, addition of polysaccharides improved the WHC of propylene glycol alginate–zein, 32 corn starch–black bean protein isolate, 50 peanut protein isolate–oat dietary fiber, 59 and ginkgo seed protein–pectin (0.1–0.5%). In addition to poor water entrapment ability (48.46–59.39%) of ginkgo seed protein compared to other plant-derived protein gels (soy or cowpea proteins), introduction of 1% pectin decreased the WHC of ginkgo seed protein–pectin gels.…”
Section: How Do Protein–polysaccharide Interactions Affect the Functi...supporting
confidence: 63%
“…These findings show that proper ultrasound pretreatment improved gel properties. The shearing and cavitation effects of ultrasonic wave exposed the hydrophobic groups amongst protein molecules, which promoted the interaction between proteins and formed a dense and uniform gel [32] . However, the decrease of gel strength may be due to the excessive expansion of MP caused by high-power or long-term ultrasound, and the conformation of protein is seriously disturbed, resulting in the formation of a poor gel network [30] .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other technologies, phacoemulsification technology has great advantages, due mainly to its energy savings, low production cost, and ease of operation and control [23] . Ultrasound is widely used in the physical processing of food, especially in recent years, and it is often used for the extraction and modification of dietary fiber, polysaccharides, protein and various food functional components [24] , [25] . Huang et al [26] found that ultrasonication and acid treatment can change the structure of SPI, reduce the particle size of protein aggregates and enhance emulsification.…”
Section: Introductionmentioning
confidence: 99%